Analisis Yuridis terhadap Pemutusan Hubungan Kerja Secara Sepihak dikarenakan Alasan Usia - Rizki Akbar Maulana; Imam Budi Santoso (Faculty of Law Hang Tuah University, 2021)
Termination of employment should not be used unilaterally because in the legislation it has been explained in depth regarding the permitted termination of employment. The purpose of this study was to analyze the case of unilateral termination of employment with reasons in accordance with Supreme Court Decision No.450/K/Pdt.Sus-PHI/2021. The reasearch method used is normative juridical with the reasearch approach used is case based by combining existing legal facts. Based on the reasearch that has been carried out, unilateral termination of employment is not permitted under the law. However, it can be allowed for certain reasons. In the case of unilateral termination of employment due to age, it is not explained in detail in the Act, but the termination must go through a negotiation process and if there is no agreement, the employer or employee can apply through the relevant institution, in this case the agency industrial relations settlement. Keywords: Employees; Work termination; Businessman; Age.